MANAGEMENT OF INTERMITTENT WATER DISTRIBUTION SYSTEMS USING GIS - WILDALI, IBRAHEM; ABU ALROB, MOHAMMAD (جامعة بوليتكنك فلسطين - مباني, 2009)
The overall shortage in water availability in most developing countries -like Palestine- necessitates intermittent supply at a low per capita supply rate. In particular they often lead to inequitable distribution of available water resources. Since these systems are water starved, consumers collect as much water as possible, quantity collected being directly related to pressure at outlets. And since pressures vary greatly in the network, quantity of water supplied is inequitable. In addition to inequities, low pressures arise because systems are designed based on low per capita allocation and with the assumption that demand is over a 24 hours at about 2.5 times average flow rate. In reality water is drawn in a shorter duration. This implies that the system suddenly becomes undersized because flows in pipes is much greater than anticipated resulting in severe pressure losses. Hence, there is generally a low-pressure regime in the network (Anand, S. and Vairavamoorthy, K. 2005). In intermittent water networks the quantity of water collected by consumers will be dependent on the driving pressure heads at the outlets and hence the relationship between the pressures in the system and the demands are important, and it cannot be assumed that demand will be met under all conditions. Therefore, the application of standard methods of network analysis to intermittent flow conditions is inappropriate and hence the need for proper management and modified design for intermittent water distribution systems (Anand, S. and Vairavamoorthy, K. 2005). Proper techniques for asset management is a huge problem faced by engineers in Palestine and GIS holds the key in helping them do this. Also by the use of web based maps of the network, the engineers in the different field offices can by cost-effective means be able to access network information. Once all the network information is stored in a GIS it makes the use of querying possible with easy and helps the planners in better understanding of the system and is able to act in a effective manner to any contingencies that may arise. Use of GIS data through Web based interfaces offers staff and engineers manage the assets in a cost-effective manner. GIS can be used as an integrated tool in processing of spatial data for the overall design and asset management of intermittent water distribution systems. (Halfawy, M. R. and Hunaidi, O. 2008). The objective of this research work is to highlight how the use of GIS will help for in both design and asset management of water intermittent water distribution systems. The reason the work concentrating on intermittent systems is that these systems are widespread in developing countries like Palestine. The project will take Halhull city in the Hebron Governorate as case study. Conventionally data on water networks will be collected and stored in paper format in GIS. The main data that will be stored will be pipe and node locations and characteristics, reservoir details, valve details, pumps, etc. The GIS contains a standard database structure to hold all the data that is regularly used for water distribution systems. Generating the mapping of distribution system for various criteria using GIS makes everyday querying based on specific criteria quick, easy and understandable for engineers. With maps and data in the system it is easy to query about all the parts of the water networks and make proper management for intermittent water distribution systems (Anand, S. and Vairavamoorthy, K. 2005). The work in its end will help the Palestinian water engineers in proper management of the physical assets of water distribution networks. In case of a water systems physical assets includes the network components such as pipelines, storage reservoirs, pumps, valves etc. The key advantages of asset management is that it enhances the knowledge of the engineers of the various assets and their details, helps in logical decision making process, it acts as a framework that provides a measure of the network performance and links it to both short and long term planning thereby helping in optimal improvement of assets at least cost.
no of pages 122, 23338, مباني 16/2009, in the store
Keywords: GIS; INTERMITTENT WATER DISTRIBUTION SYSTEMS